Supervisory Silence and Academic Ghosting in Higher Education: Hidden Threats to Students’ Mental Well-Being and Academic Flourishing – A Systematic Literature Review - Qasdussabil, Malikusshalih; Rosidi, Rofiqah (Proceedings Conference Psychology and Flourishing Humanity, 2026)
The increasing visibility of supervisory silence and academic ghosting in higher education has drawn urgent attention from scholars, counselors, and policy makers. These phenomena, which manifest through the absence of feedback or prolonged unresponsiveness from supervisors, extend beyond simple communication failures. They are systemic problems that shape the academic climate and influence the psychological resilience of students. This systematic literature review was conducted to synthesize current research and provide a more holistic understanding of how supervisory silence and ghosting affect mental well-being and academic flourishing. Searches across Scopus, Web of Science, PubMed, ScienceDirect, and Google Scholar between 2015 and 2025 generated a comprehensive set of peer-reviewed articles. Studies meeting the inclusion criteria were carefully examined and grouped thematically. The findings demonstrate that ghosting often leads to heightened stress, prolonged anxiety, feelings of abandonment, and diminished self-compassion. In parallel, supervisory silence reduces students’ sense of belonging, weakens motivation, and restricts the development of research competencies. Together, these effects hinder academic flourishing, which is understood as the ability to thrive academically, socially, and emotionally. This article argues that neglect in supervision should not be dismissed as isolated incidents, but rather viewed as hidden structural threats within higher education—risks that are intensified in post-pandemic digital environments. By framing supervisory silence and academic ghosting as complementary phenomena, this study identifies key theoretical connections, maps gaps in existing literature, and highlights the urgent need for institutions to build accountability and responsiveness into supervisory practices.